Elevated fatty acid synthase expression in prostate needle biopsy cores predicts upgraded Gleason score in radical prostatectomy specimens. Issue 1 (21st September 2013) - Hamada, Shinsuke; Horiguchi, Akio; Kuroda, Kenji; Ito, Keiichi; Asano, Tomohiko; Miyai, Kosuke; Iwaya, Keiichi
Abstract BACKGROUND We examined whether fatty acid synthase (FAS) expression in prostate biopsy cores had valuable information and could predict a Gleason score (GS) upgraded from biopsy to radical prostatectomy (RP) specimens. METHODS Immunostaining with a FAS antibody was performed on paraffin‐embedded prostate biopsy cores with GS 5–6 obtained from 80 patients who subsequently underwent RP. The correlations between FAS expression and clinicopathological parameters, upgrading group, and clinicopathological parameters including FAS expression were analyzed. Logistic regression analysis was performed to identify a significant set of independent predictors for upgrading GS. RESULTS A total of 46 patients (57.5%) with biopsy GS 5–6 were upgraded to GS ≥7 at RP. FAS expression was significantly associated with clinical T stage (P = 0.0232) and positive core rate (P = 0.0245). Upgrading from biopsy GS 5–6 to GS ≥7 at RP was significantly associated with clinical T stage (P = 0.0337), positive core rate (P = 0.0262), and FAS expression (P < 0.0001). FAS expression was a significant predictor for upgrading from biopsy GS 5–6 to GS ≥7 at RP in multivariate analysis (P < 0.0001; odds ratio, 12.35). FAS scores showed the largest area under the receiver‐operating characteristic curve (AUC) in preoperative parameters (AUC = 0.753). CONCLUSIONS Increased FAS expression in prostate biopsy cores could be a novel parameter for upgrading from biopsy GS 5–6 to GS ≥7 at RP. If a biopsy GS is low, the treatment strategy for patients with high FAS expression in prostate biopsy cores should be carefully determined. Prostate 74:90–96, 2014. © 2013 Wiley Periodicals, Inc.